Writing Postcommunism - Williams, D. author. aut Link
XI, 231 p.
Keywords: Moving through the elegiac ruins of the Berlin Wall and the Yugoslav disintegration, Writing Postcommunism explores literary evocations of the pervasive disappointment and mourning that have marked the postcommunist twilight.